2023
DOI: 10.1111/jdv.18951
|View full text |Cite
|
Sign up to set email alerts
|

Improved methodology in determining melanoma mortality and selecting patients for immunotherapy

Abstract: Improved methodology in determining melanoma mortality and selecting patients for immunotherapyDear Editor, Sentinel lymph node biopsy (SLNB) benefits are said to include identifying the presence and degree of micrometastases, improving staging, predicting prognosis and determining eligibility for adjuvant drug therapy. Sentinel lymph node biopsy is an invasive procedure, which needs nuclear medicine and operating room facilities. Neither SLNB nor early identification of micrometastases provides an overall sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…For older patients, the BAUSSS biomarker provides superior mortality prediction than SLNB and hence the potential for benefit from ADT. 13 This concern extends to 60 to 79-year-old patients with melanoma over 1 mm thickness. Gene profiling is emerging as a further prognostic tool to assist refining which melanoma patients are at high-risk.…”
Section: -Year-old Patients Standardized Hazard Ratiosmentioning
confidence: 99%
“…For older patients, the BAUSSS biomarker provides superior mortality prediction than SLNB and hence the potential for benefit from ADT. 13 This concern extends to 60 to 79-year-old patients with melanoma over 1 mm thickness. Gene profiling is emerging as a further prognostic tool to assist refining which melanoma patients are at high-risk.…”
Section: -Year-old Patients Standardized Hazard Ratiosmentioning
confidence: 99%
“…Serigne N. Lo 1,2 Alexander H. R. Varey 1,2,3 Mary-Ann El Sharouni 1,4 Richard A. Scolyer 1,2,5,6 John F. Thompson 1,2,7,8 of Tissue Oncology and Diagnostic Pathology, Royal Prince Alfred Hospital and NSW Health Pathology, Sydney, New South Wales, Australia 6 Charles Perkins Centre, The University of Sydney, Sydney, New South Wales, Australia…”
Section: Data Ava I L a Bi L I T Y S Tat E M E N Tmentioning
confidence: 99%
“…Online tools for predicting melanoma survival: Including sentinel node status as a variable improves prediction accuracy Dear Editor, Three online tools for predicting survival for patients with primary cutaneous melanomas were compared in a recent report. 1 However, the conclusion that the LifeM ath. net prediction tool, which does not consider sentinel node (SN) status, was the most reliable appears to have been based on inappropriate statistical methodology.…”
Section: E T T E R T O T H E E D I T O Rmentioning
confidence: 99%
“…These results confirm tumour thickness as the single most important survival predictor for melanoma. We have previously identified that Breslow thickness, age and ulceration (BAU) are substantially more accurate than SLNB status at predicting survival outcomes 2 . BAU is likely sufficient for clinical usage in counselling individual patients on their melanoma survival prospects.…”
Section: Introductionmentioning
confidence: 99%